Are Combined Authorities in England strategic and fit for purpose?. (March 2019) - Shutt, John; Liddle, Joyce
This paper focuses on new governance arrangements in an English context and seeks to answer the question on whether or not Combined Authorities are strategic or fit for purpose. Combined Authorities are a fragmented response to changing boundaries, employment and labour markets and the desire for functional geographies to aid competition in a global world, but also a response to the UK and English devolution conundrum. The paper highlights some of the challenges and issues arising in a BREXIT era and points to some key research priorities for the future. Drawing on the findings from all papers presented in the special issue, the authors conclude that in a post BREXIT world there will be an even greater imperative for the leaders of Britain's cities and towns to simultaneously act locally and globally in developing economic development strategies to transform local economies.